Điều trị lymphôm hodgkin người lớn - Thư, Nguyễn Trần Anh; Châu, Phan Minh; Dung, Nguyễn Thị Trang; Hồng, Lê Thụy Phương; Vũ, Lưu Hùng; Hải, Nguyễn Hồng; Dũng, Phạm Xuân (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.